2013
DOI: 10.1002/bit.24842
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐cycle recovery of lactoferrin and lactoperoxidase from crude whey using fimbriated high‐capacity magnetic cation exchangers and a novel “rotor–stator” high‐gradient magnetic separator

Abstract: BACKGROUND: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. CRC incidence and mortality rates are higher among blacks than among whites, and screening rates are lower in blacks than in whites. For the current study, the authors tested 3 interventions that were intended to increase the rate of CRC screening among African Americans. METHODS: The following interventions were chosen to address evidence gaps in the Centers for Disease Control and Prevention's Guide to Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…First results from a pilot plant similar to ours were published very recently and dealt with the multicycle purification of equine chorionic Gonadotropin (eCG) using microparticles [29]. Previous publications had already reported on studies carried out with a smaller rotor stator system: Brown and collaborators showed the suitability of HGMS for a technical application [30], whereas Müller and co-authors isolated eCG and compared the HGMS process with the technically established fixed-bed chromatography [31]. Our focus lies on the application of nanoparticles (instead of micro-) and also on the optimization of relevant processing parameters to improve final purification and concentration factors.…”
Section: Introductionmentioning
confidence: 81%
“…First results from a pilot plant similar to ours were published very recently and dealt with the multicycle purification of equine chorionic Gonadotropin (eCG) using microparticles [29]. Previous publications had already reported on studies carried out with a smaller rotor stator system: Brown and collaborators showed the suitability of HGMS for a technical application [30], whereas Müller and co-authors isolated eCG and compared the HGMS process with the technically established fixed-bed chromatography [31]. Our focus lies on the application of nanoparticles (instead of micro-) and also on the optimization of relevant processing parameters to improve final purification and concentration factors.…”
Section: Introductionmentioning
confidence: 81%
“…All other chemicals were of analytical grade and buffers were prepared with demineralized (pilot-scale trial) or Millipore Milli-Q system [6][7][8][9] and heat and silica treated whey (lane 10) before (lanes 2, 3, 6, 7) and after filtration (lanes 4,5,8,9) and with (lanes 3,5,7,9) and without (lanes 2, 4, 6, 8, 10) dilution 1:4 times. Lanes ultrapure water (lab-scale).…”
Section: Surfactant and Chemicalsmentioning
confidence: 99%
“…The superparamagnetic property of the adsorbent particles allows them to be separated from large suspension volumes. However of equal importance, is that when the magnetic field is turned off they can be easily resuspended in a new buffer [5]. Another unit operation tolerating feedstocks containing solids is Aqueous TwoPhase Systems (ATPS).…”
Section: Introductionmentioning
confidence: 99%
“…High magnetic moment, nano-or micron-sized carriers with superparamagnetic behavior and various added functionalities provide advanced therapeutic, diagnostic or bioprocessing capabilities (Dave and Gao 2009;Reddy et al 2012). The strongly magnetoresponsive character and appropriate design of surface properties are among the main requirements for nano-or micro-adsorbents to be used in magnetic bio-separation processes, such as protein purification (Müller et al 2011) involving high gradient magnetic separation (HGMS) steps (Brown et al 2013). The building blocks for the fabrication V.-M. Socoliuc (*) · L. Vékás Romanian Academy-Timisoara Branch, Center for Fundamental and Advanced Technical Research,Mihai Viteazul Street 24,300223 Timisoara, of magnetoresponsive microcarriers are the subdomain magnetite nanoparticles surface coated by biocompatible molecular layers, such as carboxylic (lauric, myristic, oleic) acids, which ensure their stabilization and dispersion in an appropriate carrier liquid, to obtain stable magnetic nanofluids-the primary materials for the envisaged magnetic nanocomposites.…”
Section: Introductionmentioning
confidence: 99%